In vivo dynamics of antigen-specific regulatory T cells not predicted from behavior in vitro - Klein, Ludger (National Academy of Sciences, 2003)
Adoptive transfer of antigen-specific CD25(+)CD4(+) regulatory T cells was used to analyze the stability of their phenotype, their behavior after immunization, and their mode of suppressing cotransferred naive T cells in vivo. We found that regulatory T cells maintained their phenotype in the absence of antigen, were not anergic in vivo, and proliferated as extensively as naive CD4(+) T cells after immunization without losing their suppressive function in vivo and in vitro. In vivo, the expansion of cotransferred naive T cells was suppressed relatively late in the response such that regulatory T cells expressing mostly IL-10 but not IL-2 or IFN-γ represented the dominant subset of cells. Our results reveal properties of regulatory T cells that were not predicted from in vitro studies.